Designing a Cloud-Based Web Server Infrastructure at the Pematang Serai Village office - Kurniawan, Fahmi; Putra, Randi Rian (CV Raskha Media Group, 2025)
The cloud is a metaphor for computer networks/the internet, where the cloud represents them, abstracted from complex, hidden infrastructure. Using cloud technology, we can combine several computer devices into a single unit (cluster) and create multiple servers on a single computer device through virtualization. The Pematang Serai Village Office is one of the villages without a server network infrastructure. Currently, the village office has several computers located in each room, and they are not connected. This decentralizes the village office's data storage, sometimes making it difficult for employees to obtain the data they need for their work. For this reason, the village office needs a means to support centralized storage on a server. Therefore, the purpose of this study is to build a web server based on a cloud infrastructure. This study uses an experimental method, with experiments conducted on the Ubuntu operating system across the following research stages: literature review, network topology design, system design analysis, server network configuration, and testing. The results of this study show that a cloud-based web server can be used for centralized data storage and that the data stored on it can be accessed properly. The conclusion from this study is that it can overcome problems with centralized data storage, ensuring that data management systems in the Pematang Serai village office are better organized and that every village office employee who needs data can access it correctly, specifically for shared data.